Patterns and predictors of health service use among people with mental disorders in São Paulo metropolitan area, Brazil. (12th April 2016) - Wang, Y.-P.; Chiavegatto Filho, A. D. P.; Campanha, A. M.; Malik, A. M.; Mogadouro, M. A.; Cambraia, M.; Viana, M. C.; Andrade, L. H.
Abstract : Aims: Important transformations in psychiatric healthcare (HC) delivery have been implemented in Latin America during the beginning of 21st century. However, information on current service uses patterns is scant, obstructing the estimates and proper planning of service needs for general population. The current investigation aims to describe patterns and estimates predictors of 12-month HC use by individuals with mental disorders in São Paulo metropolitan area, Brazil. Method: Data are from São Paulo Mental Health Survey, a cross-sectional multistage representative study. Participants were face-to-face interviewed in their household, using a structured diagnostic interview, the World Mental Health Survey Initiative version of the Composite International Diagnostic Interview. A total of 5037 respondents, non-institutionalised, aged 18 years and older were interviewed. The response rate was 81.3%. We determined the percentages of individuals with 12-month DSM-IV anxiety, mood and substance disorders that received treatment in the 12 months prior to assessment in main service sectors (specialty mental health, general medicine, human services (HS), and complementary and alternative medicine). The number of visits and percentage of individuals who received treatment at minimally adequacy also was estimated. Multilevel regression controlled contextual variables that influenced the use of service and treatment adequacy. Results: Only 10.1% of respondents used some HC service in the 12 months prior to assessment for their psychiatric problems, including 3.9% of them being treated either by a psychiatrist, 3.5% by a non-psychiatrist mental health specialist, 3.3% by a general medical (GM) provider, 1.5% by a HS provider and 1.4% by a complementary and alternative medical provider. In general, those participants who received service in the mental health specialty sector reported more visits than those in the GM sector (median 3.9 v . 1.5 visits). The cases seen in specialty sector outnumber those visiting GM treatment in terms of minimally adequate treatment (54.6 v . 23.2%). The likelihood of receiving treatment was significantly greater among individuals diagnosed with any anxiety and mood disorder, presenting more severe disorders, and with possession of HC insurance. Conclusions: The great majority of individuals with an active mental disorder in São Paulo were either untreated or insufficiently treated. Awareness and training programmes to GM professionals are advocated to improve recognition, care take and referral to specialty care when needed. Proper integration among HC sectors is recommended.